Grief and pain in Ancient Egyptian literature (Journal of the College of Basic Education, 2023)
manifestation of grumbling or less a form of a sense of injustice, remained the prevailing literary values in some primitive societies to being a kind of physical damage, while it appears in other societies as a kind of challenge, and so the values prevailing in society and among individuals are a motive to respond to previous experiences and Egyptian society, like the case of other civilized societies, lived situations of internal conflict And the external civilization, which was well expressed by many mythological religious and literary texts, which reflected a pattern of complaint, and reflected a manifestation of pain and pain.